The handbag as social idiom and carrier of meaning : inner self projected as outer person - Nel, Nanette Marguerite (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (VA)(Visual Arts))--University of Stellenbosch, 2009.